The discursive construction of Hudud in Malaysian blogs / Tanusha Rathakrishnan - Tanusha, Rathakrishnan (2016)
This research aims to examine the discursive construction of Hudud in Malaysian blogs in order to analyse how Hudud is represented among Malaysian bloggers; advocates and opponents of Hudud through the adaptation of the Discourse Historical Approach (DHA) (Wodak & Reisigl, 2001). While DHA is often used to represent social actors, this study attempts to adapt this approach in examining how Hudud is constructed by Malaysian bloggers; namely the referential, predicational and the argumentative strategies. This study is timely as the issue of implementing Hudud in Malaysia has brought forward much debate by Malaysians as a whole, although the law is said to be applied only on Muslims. In accordance with this, personal blogs are utilized in the analysis of these bloggers’ representations of Hudud under the ‘us vs. them’ strategies from the point of view of advocates and opponents of Hudud. Hence, this study seeks to investigate how Hudud is defined and viewed from the lens of those who are for and against Hudud; how these bloggers evaluate and attribute Hudud and lastly, the argumentation or topos applied in justifying them. The data used in this study consist of 128 posts from 20 blogs selected within the time frame of 2011 to 2014 comprising of 10 blogs written by Muslims and the other 10 by non-Muslims. Findings reveal that for the advocates of Hudud, there is the tendency of othering or dismissing others in favour of Hudud. Conversely, for those who oppose Hudud, there are notably stereotype labeling given to the law and these labels are at times presented as ‘facts’. Although this study is not without its limitation, it is hoped that this research has shed some light into the differing opinions and standpoints given to Hudud by Malaysian bloggers, which could as well serve as a platform for further researches.